In Vivo Leukocyte Changes Induced by Escherichia coli Subtilase Cytotoxin - Wang, Hui (American Society for Microbiology (ASM), 2011)
Subtilase cytotoxin (SubAB) is the prototype of a new family of AB(5) cytotoxins produced by Shiga-toxigenic Escherichia coli. Its cytotoxicity is due to its capacity to enter cells and specifically cleave the essential endoplasmic reticulum chaperone BiP. Previous studies have shown that intraperitoneal injection of mice with purified SubAB causes a pathology that overlaps with that seen in human cases of hemolytic-uremic syndrome, as well as dramatic splenic atrophy, suggesting that leukocytes are targeted. Here we investigated SubAB-induced leukocyte changes in the peritoneal cavity, blood, and spleen. After intraperitoneal injection, SubAB bound peritoneal leukocytes (including T and B lymphocytes, neutrophils, and macrophages). SubAB elicited marked leukocytosis, which peaked at 24 h, and increased neutrophil activation in the blood and peritoneal cavity. It also induced a marked redistribution of leukocytes among the three compartments: increases in leukocyte subpopulations in the blood and peritoneal cavity coincided with a significant decline in splenic cells. SubAB treatment also elicited significant increases in the apoptosis rates of CD4(+) T cells, B lymphocytes, and macrophages. These findings indicate that apart from direct cytotoxic effects, SubAB interacts with cellular components of both the innate and the adaptive arm of the immune system, with potential consequences for disease pathogenesis.